High levels of plasma S100A9 at admission indicate an increased risk of death in severe tuberculosis patients - Qiuyue Liu; Ru Li; Qi Li; Baojian Luo; Jun Lin; Lingna Lyu (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2021)
Objective: This study aims to evaluate plasma S100A9 levels in tuberculosis (TB) patients with admission to the ICU as a marker to predict the risk of death for pulmonary severe TB. Methods: This study enrolled 256 severe TB patients admitted to Beijing Chest Hospital from Jan to Dec 2019. The S100A9 levels were measured by ELISA. Standard clinical parameters were collected. The non-parametric Mann-Whitney test, t-test, and chi-square test were applied to statistical comparison. A multivariable analysis was performed to identify risk factors for death. Results: The plasma S100A9 levels were higher in non-survivors (25.88, 16.77–44.64) compared to survivors (15.51, 13.67–19.94). S100A9 performed better than Acute Physiology and Chronic Health Evaluation (APACHE II) score in predicting death, with AUC of 0.725, sensitivity of 65.5%, and specificity of 80.3%. By combining APACHE II score together with the S100A9 levels we got an AUC of 0.754 (95% CI 0.68 to 0.82) in predicting death. Lastly, S100A9 levels were significantly higher in patients with APACHE II score >17.5, sputum smear-positive, early death, and high cavitary lesions numbers, all of which were related to TB progression. Conclusion: Measurement and monitoring levels of plasma S100A9 in severe TB patients could facilitate the evaluation of patients with high risk at the early stage, which may help to improve the treatment outcome for TB patients.